Squalene recovery from Uzen oil field wastewater: a novel abiotic resource - Suleimen, Yerlan M.; Trofimov, Alexander N.; Mamytbekova, Gulnur K.; Kurbanaliyeva, Dilnaz; Akbay, Burkitkan; Tokay, Tursonjan (Frontiers in Environmental Chemistry, 2025)
Squalene (C30H50), a triterpene hydrocarbon, a critical precursor in the biosynthesis of cell membrane steroids, is enzymatically derived via squalene synthase in both prokaryotic and eukaryotic organisms. Its remarkable physicochemical properties and potent antioxidant characteristics underlie its extensive application across various sectors including nutraceuticals, pharmaceuticals, cosmetics, and fragrance industries. Historically, squalene has been predominantly sourced from shark liver oil and select plant oils. However, contemporary sustainable considerations have spurred pioneering investigations into unconventional reservoirs. This study reports, for the first time, the extraction of squalene from wastewater of Kazakhstan’s Uzen oil field, identifying an abiotic reservoir with significant scientific and industrial potential. In this study, wastewater samples from the Uzen oil field were collected, extracted, and the composition of dissolved volatile compounds in the extract was investigated using gas chromatography-mass spectrometry (GC-MS). Notably, the predominant constituents were hydrocarbons, which was expected. Intriguingly, the analysis also revealed substantial quantities of squalene–a natural biomarker of oil. This unexpected discovery underscores the significant promise of this unconventional source.